2020
DOI: 10.3390/met10091192
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Integration and Biological Cellular Response of SLM-Manufactured Titanium Scaffolds

Abstract: Background: SLM (Selective Laser Melting)–manufactured Titanium (Ti) scaffolds have a significant value for bone reconstructions in the oral and maxillofacial surgery field. While their mechanical properties and biocompatibility have been analysed, there is still no adequate information regarding tissue integration. Therefore, the aim of this study is a comprehensive systematic assessment of the essential parameters (porosity, pore dimension, surface treatment, shape) required to provide the long-term performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 111 publications
(217 reference statements)
0
5
0
Order By: Relevance
“… 2020 ; Băbţan et al. 2020 ), and ideal porosities ranged from approximately 70 to 90% in various studies (Shah et al. 2016 ; Băbţan et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 2020 ; Băbţan et al. 2020 ), and ideal porosities ranged from approximately 70 to 90% in various studies (Shah et al. 2016 ; Băbţan et al.…”
Section: Discussionmentioning
confidence: 98%
“…Our results are in agreement with experimental data: pores bigger than ca. 300 μm were shown to achieve good bone regeneration outcome (Zadpoor 2015;Abbasi et al 2020;Băbţan et al 2020), and ideal porosities ranged from approximately 70 to 90% in various studies (Shah et al 2016;Băbţan et al 2020;Zheng et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported that the crown marginal gap should not exceed 120 µm for clinical acceptance [17][18][19]. Comparative studies showed different results for the same material used for the manufacturing of different frameworks in terms of design, shapes, and size [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies reported different results regarding the use of the same material [20] for the fabrication of frameworks with various designs, shapes, and lengths [21,22]. The geometric discrepancies of frameworks fabricated using machining process were influenced by the accuracy in sintering contraction of pre-sintered alloys [23].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study was to systematically explore the effect of the L-PBF process parameters (laser power, scanning speed, powder layer thickness, and scanning distance) on the microstructure and compression performance of porous Ta scaffolds with 80% porosity (60-80% approaches the natural bone elasticity modulus) based on a diamond structure statistically [23]. This study can provide a reference for L-PBF process parameter optimization to obtain porous Ta scaffolds with a higher relative density and better mechanical properties.…”
Section: Introductionmentioning
confidence: 99%